Experiências Poéticas: um relato de estudos teóricos e práticas artísticas do Artista/Pesquisador (Revista Apotheke, 2015)
Ensaio Experiências Poéticas: um relato de estudos teóricos e práticas artísticas do Artista/Pesquisador